2016
DOI: 10.1007/s12574-016-0292-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac aging phenomenon and its clinical features by echocardiography

Abstract: Even in healthy subjects, the heart ages along with other organs of the body. A prominent change is progressive left ventricular (LV) diastolic dysfunction, even though LV mass increases slightly during aging. Accordingly, assessment of LV dysfunction can be employed as a surrogate marker of cardiac age. The clinical factors that may accelerate the cardiac aging process include visceral obesity, diabetes mellitus, dyslipidemia, and hypertension. At the molecular level in cardiac myocytes, reactive oxygen speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Patients with HFpEF usually are of advanced age and predominantly women with multiple comorbidities [ 2 , 3 ], and diabetes mellitus (DM) is considered a major cause of HFpEF, accounting for 20–45% of all cases [ 4 ]. DM-related cardiac dysfunction is currently defined as a form of LV diastolic dysfunction, and several studies of DM patients have identified LV diastolic dysfunction as the earliest functional alteration in the course of diabetic cardiomyopathy [ 5 8 ], which could lead to the development of HFpEF. On the other hand, LV longitudinal myocardial systolic dysfunction has been identified in DM patients with preserved LVEF but without overt coronary artery disease or HF [ 9 16 ], and some investigators reported that it may be considered the first marker of a preclinical form of DM-related cardiac dysfunction in such patients [ 9 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with HFpEF usually are of advanced age and predominantly women with multiple comorbidities [ 2 , 3 ], and diabetes mellitus (DM) is considered a major cause of HFpEF, accounting for 20–45% of all cases [ 4 ]. DM-related cardiac dysfunction is currently defined as a form of LV diastolic dysfunction, and several studies of DM patients have identified LV diastolic dysfunction as the earliest functional alteration in the course of diabetic cardiomyopathy [ 5 8 ], which could lead to the development of HFpEF. On the other hand, LV longitudinal myocardial systolic dysfunction has been identified in DM patients with preserved LVEF but without overt coronary artery disease or HF [ 9 16 ], and some investigators reported that it may be considered the first marker of a preclinical form of DM-related cardiac dysfunction in such patients [ 9 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These may include an increase of myocardial fibrosis, an increase of myocyte stiffness, changes in intra-cellular calcium homeostasis, progressive thickening of LV walls during aging, and mitochondrial oxidative stress which plays a central role in cardiac aging. 24 Regarding the sex difference, previous investigations have reported that the prevalence of heart failure with preserved ejection fraction and LV diastolic dysfunction is higher in women than in men. 23,25 Previously, it has been suggested that the lack of estrogen may cause impaired LV function in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Normal ageing is associated with reduced physiological reserve capacity in a wide range of systems responsible for responses to aerobic and muscle resistance stimuli. The normal ageing process reduces cardiac function through several pathways, with a final common pathway being diminished diastolic function associated also with mild reductions in maximal systolic function 10,11 . An age-related decline in maximal heart rate has also been observed.…”
Section: Physiological Consequences Of Ageingmentioning
confidence: 99%